Influencia del Clima Laboral en el Desempeño de los Empleados del GAD Municipal de Zaruma, 2024. - Molina Ramón, Marilyn Vanesa (2024)
The influence of the work environment on employee performance is a topic of growing interest in the business world, it refers to the perception that employees have about their work environment, a positive work environment can promote satisfaction, motivation and, consequently, improve employee performance. The present research work was conducted in the Municipality of Zaruma canton, with the objective of evaluating how the work climate influences the performance of the employees of the GAD Municipal of Zaruma canton during the year 2024, a quantitative approach and a correlational research design were adopted, data collected through surveys are analyzed, for coding and tabulation Microsoft Excel was used, the study was limited to personnel under contract under the LOSEP regime of the Municipality. The results indicated that the work climate was evaluated as "good", with an average of 3.57 (equivalent to 71.23%). The regression analysis revealed a low positive relationship between work climate and performance, with a multiple correlation coefficient of 0.3236, although this relationship is not strong, these findings allowed identifying areas to improve the work climate with low levels of satisfaction could favorably impact performance, it is recommended to continue evaluating the work climate and its impact on performance.